Adoption of climate-resilient groundnut varieties increases agricultural production, consumption, and smallholder commercialization in West Africa - Tabe-Ojong, Martin Paul Jr.; Lokossou, Jourdain C.; Gebrekidan, Bisrat; Affognon, Hippolyte D. (Springer, 2023)
As part of the climate-smart agriculture approach, the adoption of climate resilient crop varieties has the potential to build farmers’ climate resilience but could also induce agricultural transformation in developing nations. We investigate the relationship between adoption of climate-resilient groundnut varieties and production, consumption, and smallholder commercialization using panel data from Ghana, Mali, and Nigeria. We find adoption of climate resilient groundnut varieties to increase smallholder production, consumption, and commercialization. The biggest adoption impact gains are observed under the sustained use of these climate-resilient varieties. We show that adoption benefits all households, but the biggest gains are found among smaller producers, suggesting that adoption is inclusive. Furthermore, we provide suggestive evidence that yield increases could explain commercialization, although household consumption also matters. We conclude that adoption of climate-resilient groundnut varieties can at least partially reduce production constraints and promote smallholder consumption and commercialization, with implications for agricultural transformation.